ANALISIS TEMA CERITA RAKYAT BENGKULU UNTUK SISWA SEKOLAH DASAR - Muhammad Asip; Handara Tri Elitasari; Irma Yulianti Budi Safitri; Yeni Rakhmawati (As-Sibyan, 2022)
Abstract The learning process of elementary school students (SD) can be carried out using folklore. However, the folklore used for learning is not adapted to the characteristics of elementary school students. Folklore with content of violence, war, robbery, theft and so on is not appropriate to be a material for student learning. The role of the teacher is needed, to be careful in choosing the appropriate folk tales for their students. Teachers must innovate and modify folklore into teaching materials that suit the characteristics of students. Therefore, it is necessary to conduct research related to folklore that is appropriate for elementary school students. This study aims to analyze the themes of folklore for learning in elementary schools. The method used is descriptive analytic. The data source is the Bengkulu 2 folklore book by Naim Emel Prahana. The research succeeded in finding the themes of Bengkulu folklore. The themes are about patience, wisdom, intelligence, steadfastness, self-sacrifice, guarding the tongue, respecting others and mutual cooperation. Based on the results of the research found, it can be concluded that there are five stories of Bengkulu folklore that are suitable for learning and three stories that are not suitable for learning elementary school students. Keywords: Character; Folklore; Theme Abstrak Proses pembelajaran siswa sekolah dasar (SD) dapat dilakukan dengan menggunakan cerita rakyat. Namun, cerita rakyat yang digunakan untuk pembelajaran kurang disesuaikan dengan karakteritik siswa SD. Cerita rakyat dengan konten kekerasan, peperangan, perampokan, pencurian dan sebagainya tidak tepat untuk menjadi bahan pembelajaran siswa. Peran guru sangat dibutuhkan, untuk berhati-hati dalam memilih cerita rakyat yang sesuai untuk siswanya. Guru harus berinovasi dan memodifikasi cerita rakyat menjadi bahan ajar yang sesuai dengan karakteristik siswa. Oleh sebab itu, perlu dilakukan penelitian terkait cerita rakyat yang tepat untuk siswa SD. Penelitian bertujuan untuk menganalisis tema-tema cerita rakyat untuk pembelajaran di SD. Metode yang digunakan yaitu deskriptif analitik. Sumber data buku cerita rakyat Bengkulu 2 karya Naim Emel Prahana. Penelitian berhasil menemukan tema-tema cerita rakyat Bengkulu. Adapun temanya tentang kesabaran, kebijaksanaan, kecerdasan, sikap tabah, rela berkorban, menjaga lisan, menghormati orang lain dan gotong-royong. Berdasarkan hasil penelitian yang ditemukan maka dapat disimpulkan bahwa cerita rakyat Bengkulu terdapat lima cerita yang sesuai untuk pembelajaran dan tiga cerita yang kurang sesuai untuk pembelajaran siswa SD.